Dialectic and dialogue - Nikulin, D. V. (Dmitriĭ Vladimirovich) (Stanford University Press, 2010)
"Dialectic and Dialogue is a very important work, potentially a classic. It is stimulating throughout, as well as original in conception and execution--the first study to bring together these two signal concepts."--Mark Roche, University of Notre Dame.